Smart Tree Learning Media - We Can Be Based on Android For Arabic Subjects/ Media Pembelajaran Pohon Pintar-Kita Bisa Berbasis Android Untuk Matakuliah Bahasa Arab - Lilis Suaibah; Taufiqur Rahman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aims to: (1) determine the design process of learning media Smart Tree-We Can (Rule, Arabic Vocabulary of Islamic Economics) based on android applications on vocabulary material (mufrodat) and Arabic rules, (2). Knowing the effectiveness of learning Arabic by using learning media, Smart Tree-We Can be based on Android applications. The trial subjects in this study were 1110 3rd semester students taking Arabic courses at the Trunojoyo University Madura Islamic Studies Program. The results showed: (1) the learning process of the design of learning media Smart Tree-We Can be based on android applications consisting of four phases, namely the investigation phase, the design phase, the realization phase and the fifth is the evaluation and revision phase (2). Smart Tree-We Can learn media based on android applications is considered useful in increasing students' motivation and understanding of the rules and vocabulary of Arabic Sharia Economics.